Cell type‐dependent functions of microRNA‐92a. Issue 7 (25th March 2018) - Kohram, Fatemeh; Fallah, Parviz; Shamsara, Mehdi; Bolandi, Zohreh; Rassoulzadegan, Minoo; Soleimani, Masoud; Ghanbarian, Hossein
Abstract: The role of miR‐17/92 family in development and progression of various cancers has been established. The members of this miRNA family have been shown to be over expressed and target various genes within proliferation, metastasis and angiogenesis pathways. Although all members might be overexpressed in a certain cancer type, only certain members of the family may have roles in progression of that cancer. In this study, we have chosen miR‐92a, a member of the miR‐17/92 family to compare its function in three different cancer cell lines. HL60, MCF7, and Jurkat cell lines were transduced with miR‐92a and proliferation and apoptosis was measured in these cells by cell count, MTT, and caspase assays. Although in comparison to pre‐miR‐17/92, the level of miR‐92a is higher in Jurkat cells compared to MCF7 and HL60 cells, here we have shown that increasing miR‐92a levels results in apoptosis in Jurkat cells and proliferation in MCF7 and HL60 cells. miR‐92a was also microinjected into mice fertilized eggs and after dissection, apoptosis was only observed in white pulp of spleen that is mainly made up of white blood cells. Our results show that miR‐92a possesses a cell‐type dependent function. Abstract : We have shown that increasing miR‐92a levels results in apoptosis in Jurkat cells and proliferation in MCF7 and HL60 cells. miR‐92a was also microinjected into mice fertilized eggs and after dissection, apoptosis was only observed in white pulp of spleen that is mainly made up of white blood cells. Our results show that miR‐92a possesses a cell‐type dependent function.